High-pressure-resistant gas storage cavern sealing composite material and preparation method thereof

By introducing modified activated rubber powder and nano SiO2 into the sealing materials of the air-cave chamber and adopting thermal insulation and ultrasonic vibration technology, the problem of poor sealing performance of traditional sealing materials in high-pressure and high-temperature environments is solved, achieving high efficiency and economical The sealing effect of the air storage chamber significantly improves the safety and service life of the air storage chamber.

CN119391141APending Publication Date: 2025-02-07POWER CHINA KUNMING ENG CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411732705.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional air-storage chamber sealing materials have poor sealing performance under high pressure and high temperature environments and are costly, which affects the structural safety and service life of the air-storage chamber.

Method used

Develop a high-pressure-resistant air-cave chamber sealing composite material. By introducing modified activated rubber powder, nano SiO2 and other components into epoxy resin, combined with insulation and ultrasonic vibration technology, it produces excellent mechanical properties and weathering resistance. sealing material.

Benefits of technology

It significantly improves the sealing performance and safety of the air storage chamber, reduces the price and construction difficulty of sealing materials, extends the service life of the materials, and is suitable for high-temperature gas storage environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391141A_ABST
    Figure CN119391141A_ABST
Patent Text Reader

Abstract

The invention discloses a high-pressure-resistant gas storage cavern sealing composite material and a preparation method, and relates to the technical field of gas storage cavern sealing materials.The high-pressure-resistant gas storage cavern sealing composite material is prepared from a component A and a component B, the component A comprises the following components in parts by weight: 100 parts of epoxy resin, 40-50 parts of 4-tert-butylphenyl glycidyl ether, 10-20 parts of dioctyl phthalate, 2-5 parts of modified activated rubber powder, 1-2 parts of a coupling agent, 1-3 parts of nano SiO2 and 2-5 parts of an anti-aging agent; the component B is prepared from 15 to 20 parts of triethylene tetramine, 5 to 15 parts of 2, 4, 6-tri (dimethylaminomethyl) phenol, 2 to 4 parts of polyamide, 0.5 to 1 part of silicon-copper sealant and 3 to 5 parts of polydimethylsiloxane. According to the high-pressure-resistant gas storage cavern sealing composite material, the sealing performance and safety of a gas storage cavern can be enhanced, the problems that an existing traditional sealing material is poor in durability, poor in high pressure resistance, high in manufacturing cost and the like are solved, reliable guarantee is provided for safe and stable operation of underground gas storage facilities, and engineering investment is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas storage cavern sealing materials, and in particular to a high-pressure resistant gas storage cavern sealing composite material and a preparation method thereof. Background Art

[0002] As an important gas storage facility in the underground reservoir, the gas storage cavern undertakes the important function of storing and releasing gas. However, due to the harsh environment, high pressure, and large temperature changes of the underground reservoir, the traditional gas storage cavern sealing materials are easily corroded and penetrated by high-pressure gas, resulting in a decrease in the sealing performance of the cavern and a decrease in operating efficiency, affecting the structural safety and service life of the cavern. At present, the most commonly used solution is to fill the concrete with steel lining, and use the airtightness of the steel material to seal the gas storage cavern to store gas. However, when the steel lining is used to seal the gas storage cavern to store gas, the steel lining is easily corroded by groundwater, and the gas storage cavern is prone to penetration, especially under high temperature and high pressure conditions, which affects the sealing effect of the gas storage cavern; secondly, the steel lining is expensive as a sealing material for the gas storage cavern, and accounts for a high proportion of the investment in the gas storage cavern project.

[0003] Therefore, in order to solve the problem of poor sealing performance of traditional gas storage cavern sealing materials under high pressure and high temperature environments, and to improve the economic efficiency of the project, researchers began to explore new high-pressure resistant sealing composite materials, thereby increasing the maximum gas storage pressure of underground gas storage, increasing the gas storage capacity, and ensuring the sealing performance and safety of the gas storage caverns. Summary of the invention

[0004] The main purpose of the present invention is to provide a high-pressure resistant gas storage cavern sealing composite material and a preparation method. The high-pressure resistant gas storage cavern sealing composite material can enhance the sealing performance and safety of the gas storage cavern, solve the problems of poor durability, high pressure difference resistance, high cost, etc. of current traditional sealing materials, provide reliable guarantee for the safe and stable operation of underground gas storage facilities, and significantly reduce project investment.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In one aspect, the present invention provides a high-pressure resistant gas storage cavern sealing composite material. The raw material components for preparing the high-pressure resistant gas storage cavern sealing composite material include component A and component B, which are calculated by weight:

[0007] The component A comprises 100 parts of epoxy resin, 40-50 parts of 4-tert-butylphenyl glycidyl ether, 10-20 parts of dioctyl phthalate, 2-5 parts of modified activated rubber powder, 1-2 parts of coupling agent, 1-3 parts of nano-SiO2 and 2-5 parts of anti-aging agent;

[0008] The B component comprises 15-20 parts of triethylenetetramine, 5-15 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 2-4 parts of polyamide, 0.5-1 part of silicon copper sealant and 3-5 parts of polydimethylsiloxane.

[0009] The high-pressure gas storage cavern sealing composite material not only has excellent mechanical properties, but also has excellent properties such as low air permeability, good thermal stability, and weather aging resistance. At the same time, it greatly reduces the price of sealing materials and construction difficulty in the material design and cost process, and improves the construction cost of the gas storage cavern. Therefore, researching and developing this new material has important theoretical significance and practical value.

[0010] Preferably, the epoxy resin is bisphenol A epoxy resin.

[0011] Specifically, the bisphenol A type epoxy resin may be at least one of AE-35, E-42, E-44, E-51 and E-55.

[0012] Preferably, the coupling agent is one of KH550 silane coupling agent, KH560 silane coupling agent or γ-(2,3-epoxypropoxy)propyltrimethoxysilane; the particle size of the nano-SiO2 is 40 to 100 nm, and the nano-SiO2 is white powder.

[0013] Preferably, the anti-aging agent is one of pentaerythritol tetrakis[B-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, trisnonylphenyl phosphite, tris(2,4-di-tert-butylphenyl)phosphite or 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol.

[0014] Preferably, the polyamide is an aliphatic modified amide with a molecular weight of 115-650.

[0015] Preferably, the modified activated rubber powder is obtained by modifying and activating waste tires after crushing, and the particle size of the modified activated rubber powder is 80-120 meshes.

[0016] In another aspect, the present invention provides a method for preparing a high-pressure resistant gas storage cavern sealing composite material, comprising the following steps:

[0017] (1) 4-tert-butylphenyl glycidyl ether and dioctyl phthalate are sequentially added to epoxy resin and stirred for the first time, and then modified activated rubber powder and coupling agent are added and stirred for the second time to obtain a mixed solution; the mixed solution is placed in an oil bath pot and stirred for 4 to 6 minutes in an oil bath, and then an anti-aging agent and nano-SiO2 are added to the system and stirred for the third time to obtain component A;

[0018] (2) mixing triethylenetetramine, 2,4,6-tris(dimethylaminomethyl)phenol, polyamide, silicon copper sealant and polydimethylsiloxane and stirring for the fourth time to obtain component B;

[0019] (3) The temperature of component B is raised to a certain temperature and kept warm before being stirred for the fifth time, component A is poured into the stirred component B, and then an ultrasonic vibrator is used to vibrate for 2 to 4 minutes to obtain a modified activated rubber powder modified high-toughness epoxy mortar material.

[0020] Specifically, by using heat preservation and ultrasonic vibration technology in the epoxy system, the purpose of heat preservation is to balance the reaction system, thereby increasing the intermolecular forces between the components and playing a catalytic effect; at the same time, heat preservation can promote the high energy state of the molecules of the reactants, increase the collision frequency and energy between them, and facilitate the reaction; ultrasonic vibration can generate local high pressure and collision probability, accelerate the material transfer and mass transfer process, promote the mixing and diffusion of the reactants, and thus improve the reaction efficiency.

[0021] Preferably, the preparation method of the modified activated rubber powder is as follows: after crushing the waste tires, add 8% NaOH solution and stir for 2-3 hours, then filter and remove the filtrate to obtain a filter residue; add 90-110ml of 0.010mol / LKMnO4 solution to the filter residue and stir for 3-5 hours, filter out the solution and obtain the modified activated rubber powder. The modified activated rubber powder is made from waste tires, and mainly includes polyisoprene, polybutadiene, styrene butadiene copolymer and polyisobutylene. Taking polyisoprene as an example, as shown in the following reaction formula, a modified activated rubber powder containing hydroxyl, ether bond and carboxyl groups on the surface can be obtained; after treatment, the modified activated rubber powder can be more easily dispersed in the epoxy system and well combined through intermolecular forces.

[0022]

[0023] Specifically, the introduction of modified activated rubber powder can make the sealing material: (1) Microstructure change: The introduction of modified activated rubber powder will form a composite dispersed phase in the epoxy resin matrix. These rubber particles can fill the micropores and surface unevenness of the epoxy resin to form a dense network structure. This microstructure is conducive to preventing the penetration of liquids, gases and other media into the material and improving the sealing performance of the material. (2) Interface compatibility and affinity: The modified activated rubber powder has good interface compatibility, improves good interface affinity, increases the bonding strength between the two, and further improves the sealing performance. (3) Temperature effect: The introduction of modified activated rubber powder can reduce the exothermic temperature peak of the polymerization reaction of the epoxy system, reduce the reaction rate, and improve the cross-linking system reaction of the material. At the same time, since rubber has good heat resistance, introducing it into epoxy resin can enhance the heat resistance of the material, so that the material can still maintain good sealing performance under high temperature environment. (4) Chemical reaction effect: The introduction of rubber powder can affect the chemical reaction characteristics of epoxy resin. Rubber powder has good chemical stability, which can slow down the chemical reaction rate between epoxy resin and surrounding media, thus prolonging the service life of the material. In addition, rubber powder can also provide additional fillers, increase the corrosion resistance of the material, prevent the erosion of the epoxy resin system by the media, and improve the durability of the sealing performance.

[0024] Preferably, the mass volume ratio of waste tires to NaOH solution is 10-15:1 g / L.

[0025] Preferably, the rotation speeds of the first stirring, the second stirring, the third stirring, the fourth stirring, and the fifth stirring are all 300-400 rpm, and the stirring time is all 2-4 min.

[0026] Preferably, the insulation temperature in step (1) is 40-55° C., the insulation temperature in step (3) is 35-45° C.; and the frequency of the ultrasonic vibrator is 20-130 KHZ.

[0027] The beneficial effects of the present invention are:

[0028] (1) The epoxy resin of the present invention has excellent mechanical properties, and the modified activated rubber powder has good airtightness, elasticity and deformation properties. After compounding, it can better perform reinforcement, improve the sealing effect, and increase its sealing effect under high pressure conditions. At the same time, both the epoxy resin and the rubber powder have corrosion resistance. After compounding, the corrosion resistance of the sealing material can be improved and the service life can be extended.

[0029] (2) Nano-silicon dioxide as a filler can increase the hardness and wear resistance of the sealing material, making it more durable and wear-resistant. It can also improve the compression resistance of the sealing material. At the same time, nano-silicon dioxide has excellent high temperature resistance. After addition, it can improve the heat resistance of the sealing material and is suitable for high temperature gas storage environments.

[0030] (3) The new high-pressure resistant sealing composite material used for the gas storage cavern is an epoxy system material with low viscosity and long operability time. It can be constructed using existing mature chemical grouting, curtain grouting and other technologies, which greatly reduces the construction difficulty. At the same time, the introduction of modified activated rubber powder as solid waste will greatly reduce the price of epoxy materials and realize the reuse of solid waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A scene graph for use in preparing materials for an embodiment of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0033] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0034] Example 1

[0035] This embodiment provides a high-pressure resistant gas storage cavern sealing composite material and a preparation method thereof. The raw material components for preparing the high-pressure resistant gas storage cavern sealing composite material are:

[0036] 100 parts of bisphenol A E44 type epoxy resin, 40 parts of 4-tert-butylphenyl glycidyl ether, 10 parts of dioctyl phthalate: 2 parts of 60-mesh modified activated rubber powder (the main component is polyisoprene), 1.5 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent (solid), 1 part of nano-SiO2 with a particle size of 40nm (SiO2 spheres), 2 parts of tetrakis[B-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester antioxidant, 15 parts of triethylenetetramine (AR, 70%), 15 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 2 parts of aliphatic polyamide with a molecular weight of 65, 0.5 parts of silicon copper sealant, and 3 parts of polydimethylsiloxane.

[0037] The preparation method of the high-pressure resistant gas storage cavern sealing composite material comprises the following steps:

[0038] (1) 40 parts of 4-tert-butylphenyl glycidyl ether and 10 parts of dioctyl phthalate were added to 100 parts of bisphenol A E44 epoxy resin in sequence, and the mixture was stirred at 350 rpm for 3 minutes using a magnetic stirrer. Then, 2 parts of 60-mesh modified activated rubber powder and 1.5 parts of γ-(2,3-epoxypropoxy)propyl trimethoxysilane coupling agent were added, and the mixture was stirred at 400 rpm for 4 minutes using a magnetic stirrer. The mixture was placed in a 45°C oil bath and stirred for 5 minutes. Then, 2 parts of tetrakis[B-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester antioxidant and 1 part of nano-SiO2 with a particle size of 40 nm were added to the system, and the mixture was stirred at 300 rpm for 2 minutes using a magnetic stirrer to obtain component A.

[0039] (2) 15 parts of triethylenetetramine, 15 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 2 parts of aliphatic polyamide with a molecular weight of 65, 0.5 parts of silicon copper sealant and 3 parts of polydimethylsiloxane were stirred at 350 rpm for 3 minutes using a magnetic stirrer and then added to component B.

[0040] (3) After the temperature of component B is raised to 40°C and kept warm for 5 minutes, component A is poured into the stirred component B, stirred at 350 rpm for 3 minutes, and then vibrated at 80 kHz for 3 minutes using an ultrasonic vibrator to obtain a high-toughness epoxy mortar material modified with modified activated rubber powder.

[0041] The preparation method of modified activated rubber powder is as follows: after crushing 15g of waste tires, adding 8% NaOH solution and stirring for 3h, filtering and removing the filtrate to obtain filter residue; adding 0.010mol / L100ml KMnO4 solution to the filter residue and stirring for 5h, filtering out the solution to obtain modified activated rubber powder.

[0042] The obtained high-toughness epoxy mortar material modified with modified activated rubber powder is mainly used in caverns, containers and all gas storage spaces where gas storage is required. Its function is to increase its high-pressure resistance, easy construction and low cost on the basis of ensuring high strength.

[0043] The use scenarios of the materials prepared in this embodiment are as follows Figure 1As shown, the high-pressure gas storage cavern sealing composite material is arranged between two layers of concrete. Outer concrete: The outer concrete is the first structural barrier of the gas storage cavern, with high strength and good compressive resistance. Its main function is to bear external loads and protect the internal sealing structure. High-pressure gas storage cavern sealing composite material layer: The sealing composite material layer is arranged between the outer concrete and the inner concrete, playing a key sealing role. In the figure, the sealing composite material layer is depicted as a continuous and evenly distributed layer between the two layers of concrete. Inner concrete: The inner concrete is the second structural barrier of the gas storage cavern, also with high strength and good compressive resistance. It forms a solid structure with the outer concrete to bear the pressure of the internal high-pressure gas together. The inner concrete also plays the role of protecting the sealing composite material layer to prevent it from mechanical damage or chemical erosion. When the high-toughness epoxy mortar material modified by modified activated rubber powder is used in the gas storage cavern, the high-pressure gas storage cavern sealing composite material is arranged between the two layers of concrete, playing a key sealing role. The outer and inner concrete layers form a strong structure that bears the pressure of the high-pressure gas inside. The inner concrete layer also protects the sealing composite layer from mechanical damage or chemical erosion.

[0044] Example 2

[0045] This embodiment provides a high-pressure resistant gas storage cavern sealing composite material and a preparation method thereof. The raw material components for preparing the high-pressure resistant gas storage cavern sealing composite material are:

[0046] 100 parts of bisphenol A E44 type epoxy resin, 45 parts of 4-tert-butylphenyl glycidyl ether, 20 parts of dioctyl phthalate, 3 parts of 80-mesh modified activated rubber powder (the main component is polyisoprene), 2 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent (solid), 2 parts of nano-SiO2 with a particle size of 60nm (SiO2 spheres), 3 parts of trinonylphenyl phosphite antioxidant, 17 parts of triethylenetetramine (AR, 70%), 5 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 3 parts of aliphatic polyamide with a molecular weight of 650, 0.8 parts of silicon copper sealant, and 4 parts of polydimethylsiloxane.

[0047] The preparation method of the high-pressure resistant gas storage cavern sealing composite material comprises the following steps:

[0048] (1) 45 parts of 4-tert-butylphenyl glycidyl ether and 20 parts of dioctyl phthalate were added to 100 parts of bisphenol A E44 epoxy resin in sequence, and the mixture was stirred at 350 rpm for 3 minutes using a magnetic stirrer. Then, 3 parts of 80-mesh modified activated rubber powder and 2 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent were added, and the mixture was stirred at 400 rpm for 4 minutes using a magnetic stirrer. The mixture was placed in a 45°C oil bath and kept stirred for 6 minutes. Then, 3 parts of trinonylphenyl phosphite antioxidant and 2 parts of nano-SiO2 with a particle size of 60 nm were added to the system, and the mixture was stirred at 300 rpm for 2 minutes using a magnetic stirrer to obtain component A.

[0049] (2) 17 parts of triethylenetetramine, 5 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 3 parts of aliphatic polyamide with a molecular weight of 650, 0.8 parts of silicon copper sealant and 4 parts of polydimethylsiloxane were stirred at 350 rpm using a magnetic stirrer for 3 minutes and then added to component B.

[0050] (3) After the temperature of component B is raised to 40°C and kept warm for 5 minutes, component A is poured into the stirred component B, stirred at 350 rpm for 3 minutes, and then vibrated at 80 kHz for 2 minutes using an ultrasonic vibrator to obtain a modified activated rubber powder modified high-toughness epoxy mortar material.

[0051] The preparation method of modified activated rubber powder is as follows: after crushing 15g of waste tires, adding 8% NaOH solution and stirring for 2h, filtering and removing the filtrate to obtain filter residue; adding 0.010mol / L100ml KMnO4 solution to the filter residue and stirring for 4h, filtering out the solution to obtain modified activated rubber powder.

[0052] Example 3

[0053] This embodiment provides a high-pressure resistant gas storage cavern sealing composite material and a preparation method thereof. The raw material components for preparing the high-pressure resistant gas storage cavern sealing composite material are:

[0054] 100 parts of bisphenol A E44 type epoxy resin, 50 parts of 4-tert-butylphenyl glycidyl ether, 15 parts of dioctyl phthalate, 5 parts of 120 mesh modified activated rubber powder (the main component is polyisoprene), 1 part of KH560 silane coupling agent (solid), 3 parts of nano-SiO2 (SiO2 spheres) with a particle size of 100nm, 5 parts of tris (2,4-di-tert-butylphenyl) phosphite antioxidant, 20 parts of triethylenetetramine (AR, 70%), 10 parts of 2,4,6-tris (dimethylaminomethyl) phenol, 4 parts of aliphatic polyamide with a molecular weight of 650, 1 part of silicon copper sealant, and 5 parts of polydimethylsiloxane.

[0055] The preparation method of the high-pressure resistant gas storage cavern sealing composite material comprises the following steps:

[0056] (1) 50 parts of 4-tert-butylphenyl glycidyl ether and 15 parts of dioctyl phthalate were added to 100 parts of bisphenol A E44 epoxy resin in sequence, and stirred at 350 rpm for 3 minutes using a magnetic stirrer. Then, 5 parts of 120-mesh modified activated rubber powder and 1 part of KH560 silane coupling agent were added, and stirred at 400 rpm for 4 minutes using a magnetic stirrer. The mixture was placed in a 40°C oil bath and stirred for 4 minutes. Then, 5 parts of tris(2,4-di-tert-butylphenyl)phosphite antioxidant and 3 parts of nano-SiO2 with a particle size of 100 nm were added to the system, and stirred at 300 rpm for 2 minutes using a magnetic stirrer to obtain component A.

[0057] (2) 20 parts of triethylenetetramine, 10 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 4 parts of aliphatic polyamide with a molecular weight of 650, 1 part of silicon copper sealant and 5 parts of polydimethylsiloxane were stirred at 350 rpm using a magnetic stirrer for 3 minutes and then added to component B.

[0058] (3) After the temperature of component B is raised to 40°C and kept warm for 5 minutes, component A is poured into the stirred component B, stirred at 350 rpm for 3 minutes, and then vibrated at 20 kHz for 4 minutes using an ultrasonic vibrator to obtain a modified activated rubber powder modified high-toughness epoxy mortar material.

[0059] The preparation method of modified activated rubber powder is as follows: after crushing 10g of waste tires, adding 1L8% NaOH solution, stirring for 3h, filtering, removing the filtrate, and obtaining filter residue; adding 0.010mol / L100ml KMnO4 solution to the filter residue, stirring for 3h, filtering out the solution, and obtaining modified activated rubber powder.

[0060] Comparative Example 1

[0061] The difference between this comparative example and Example 1 is that the rubber powder is not activated, and non-activated rubber powder is directly used.

[0062] Comparative Example 2

[0063] The difference between this comparative example and Example 1 is that no modified activated rubber powder is added.

[0064] Comparative Example 3

[0065] The difference between this comparative example and Example 1 is that modified activated rubber powder and nano-SiO2 are not added.

[0066] The protective materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests. The specific test methods and test results are as follows: After the A and B components were mixed evenly, the test was cured at 23°C ± 2°C and 50% ± 5% RH. The compressive strength, tensile strength, elongation at break and bonding strength of the product were tested using an electronic universal testing machine. A gas permeameter was used to measure the air permeability (23.5°C) and the single-day air leakage rate was measured under a sliding pressure range of 8MPa to 14MPa. All performance items were cured for 28 days, and the results are shown in Table 1.

[0067] Table 1: Material performance test table

[0068]

[0069] It can be seen from Table 1 that the consolidated body obtained in Example 1 of the present invention has significantly better compressive strength, tensile strength, elongation at break and bonding strength than those in Comparative Examples 1 to 3, and its strength in the age period far exceeds the compressive strength level of concrete used in construction by more than 40 MPa. At the same time, the air permeability and single-day gas leakage rate are as low as 0.3 ml / (s·cm 2 cm×10 -8 ) and 0.41%, and at the same time have high high pressure resistance. Since comparative example 1 does not add activation, the bonding between rubber powder and epoxy system is poor, resulting in performance degradation; secondly, comparative examples 2 to 3 do not add modified activated rubber powder and nano-SiO2, although the strength of the material is increased, the air tightness to air is poor and the leakage rate is high.

[0070] Example 4

[0071] This embodiment provides a high-pressure resistant gas storage cavern sealing composite material and a preparation method thereof. The raw material components for preparing the high-pressure resistant gas storage cavern sealing composite material are:

[0072] 100 parts of bisphenol A E44 type epoxy resin, 35 parts of 4-tert-butylphenyl glycidyl ether, 15 parts of dioctyl phthalate, 3 parts of 60 mesh modified activated rubber powder (the main component is polyisoprene), 1.5 parts of KH550 silane coupling agent (solid), 2 parts of nano-SiO2 (SiO2 spheres) with a particle size of 100nm, 5 parts of 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol antioxidant, 20 parts of triethylenetetramine (AR, 70%), 10 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 4 parts of aliphatic polyamide with a molecular weight of 650, 1 part of silicon copper sealant, and 5 parts of polydimethylsiloxane.

[0073] The preparation method of the high-pressure resistant gas storage cavern sealing composite material comprises the following steps:

[0074] (1) 35 parts of 4-tert-butylphenyl glycidyl ether and 15 parts of dioctyl phthalate were added to 100 parts of bisphenol A E44 epoxy resin in sequence, and stirred at 300 rpm for 3 minutes using a magnetic stirrer. Then, 3 parts of 60-mesh modified activated rubber powder and 1.5 parts of KH550 silane coupling agent were added, and stirred at 350 rpm for 4 minutes using a magnetic stirrer. The mixture was placed in a 50°C oil bath and stirred for 5 minutes. Then, 2 parts of 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol antioxidant and 2 parts of nano-SiO2 with a particle size of 100 nm were added to the system, and stirred at 300 rpm for 2 minutes using a magnetic stirrer to obtain component A.

[0075] (2) 20 parts of triethylenetetramine, 10 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 4 parts of aliphatic polyamide with a molecular weight of 650, 1 part of silicon copper sealant and 5 parts of polydimethylsiloxane were stirred at 400 rpm using a magnetic stirrer for 4 minutes and then added to component B.

[0076] (3) After the temperature of component B is raised to 55° C. and kept warm for 3 minutes, component A is poured into the stirred component B, stirred at 300 rpm for 2 minutes, and then vibrated at 130 kHz for 3 minutes using an ultrasonic vibrator to obtain a high-toughness epoxy mortar material modified with modified activated rubber powder.

[0077] The preparation method of modified activated rubber powder is as follows: after crushing 12g of waste tires, adding 1L8% NaOH solution, stirring for 3h, filtering, removing the filtrate, and obtaining filter residue; adding 0.010mol / L100ml KMnO4 solution to the filter residue, stirring for 3h, filtering out the solution, and obtaining modified activated rubber powder.

[0078] In summary, the high-pressure resistant gas storage cavern sealing composite material of the present invention not only has excellent mechanical properties but also has excellent properties such as low air permeability, good thermal stability, and weather aging resistance, and at the same time, it greatly reduces the price of sealing materials in the material design and cost process, reduces the construction difficulty, and improves the construction cost of the gas storage cavern. Therefore, researching and developing this new material has important theoretical significance and practical value.

[0079] The specific implementation methods of the invention are described in detail above, but they are only examples, and the invention is not limited to the specific implementation methods described above. For those skilled in the art, any equivalent modification or substitution of the invention is also within the scope of the invention, therefore, the equalization, modification, improvement, etc. made without departing from the spirit and principle of the invention should be included in the scope of the invention.

Claims

1. A high-pressure resistant gas storage cavern sealing composite material, characterized in that: The raw material components for preparing the high-pressure resistant gas storage cavern sealing composite material include component A and component B, calculated by weight: The component A comprises 100 parts of epoxy resin, 40-50 parts of 4-tert-butylphenyl glycidyl ether, 10-20 parts of dioctyl phthalate, 2-5 parts of modified activated rubber powder, 1-2 parts of coupling agent, 1-3 parts of nano-SiO2 and 2-5 parts of anti-aging agent; The B component comprises 15-20 parts of triethylenetetramine, 5-15 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 2-4 parts of polyamide, 0.5-1 part of silicon copper sealant and 3-5 parts of polydimethylsiloxane.

2. The high pressure resistant gas storage cavern sealing composite material according to claim 1, characterized in that: The epoxy resin is bisphenol A type epoxy resin.

3. The high pressure resistant gas storage cavern sealing composite material according to claim 1, characterized in that: The coupling agent is one of KH550 silane coupling agent, KH560 silane coupling agent or γ-(2,3-epoxypropoxy)propyltrimethoxysilane; and the particle size of the nano-SiO2 is 40-100 nm.

4. The high pressure resistant gas storage cavern sealing composite material according to claim 1, characterized in that: The anti-aging agent is one of tetrakis[B-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, trisnonylphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite or 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol.

5. The high pressure resistant gas storage cavern sealing composite material according to claim 1, characterized in that: The polyamide is an aliphatic modified amide with a molecular weight of 115-650.

6. The high pressure resistant gas storage cavern sealing composite material according to claim 1, characterized in that: The modified activated rubber powder is obtained by modifying and activating waste tires after being crushed, and the particle size of the modified activated rubber powder is 80-120 meshes.

7. A method for preparing the high-pressure resistant gas storage cavern sealing composite material according to any one of claims 1 to 6, characterized in that: The steps include: (1) 4-tert-butylphenyl glycidyl ether and dioctyl phthalate are sequentially added to epoxy resin and stirred for the first time, and then modified activated rubber powder and coupling agent are added and stirred for the second time to obtain a mixed solution; the mixed solution is placed in an oil bath pot and stirred for 4 to 6 minutes in an oil bath, and then an anti-aging agent and nano-SiO2 are added to the system and stirred for the third time to obtain component A; (2) mixing triethylenetetramine, 2,4,6-tris(dimethylaminomethyl)phenol, polyamide, silicon copper sealant and polydimethylsiloxane and stirring for the fourth time to obtain component B; (3) The temperature of component B is raised to a certain temperature and kept warm before being stirred for the fifth time, component A is poured into the stirred component B, and then an ultrasonic vibrator is used to vibrate for 2 to 4 minutes to obtain a modified activated rubber powder modified high-toughness epoxy mortar material.

8. The method for preparing the high-pressure resistant gas storage cavern sealing composite material according to claim 7, characterized in that: The preparation method of the modified activated rubber powder is as follows: after crushing the waste tire, adding 8% NaOH solution, stirring for 2-3 hours, filtering, removing the filtrate, and obtaining filter residue; adding 90-110 ml of 0.010 mol / L KMnO4 solution to the filter residue, stirring for 3-5 hours, filtering out the solution, and obtaining the modified activated rubber powder.

9. The method for preparing the high-pressure resistant gas storage cavern sealing composite material according to claim 8, characterized in that: The mass volume ratio of waste tires to NaOH solution is 10-15:1 g / L.

10. The method for preparing the high-pressure resistant gas storage cavern sealing composite material according to claim 7, characterized in that: The rotation speeds of the first stirring, the second stirring, the third stirring, the fourth stirring and the fifth stirring are all 300-400 rpm, and the stirring time is all 2-4 min.